2009
DOI: 10.1097/pts.0b013e3181bd1c2a
|View full text |Cite
|
Sign up to set email alerts
|

The Human Factors of Home Health Care

Abstract: By examining the major components and interdependencies of the home health care delivery system, a human factors perspective offers insights into ways that safety and quality can be compromised and can help pave the way for new modes of thinking in home health care policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 32 publications
(14 reference statements)
1
34
0
Order By: Relevance
“…The study identified four main actors, ten actions, and 37 unique artifacts across seven major types, all contributing to 21 possible patient care and work outcomes. Like other HFE studies of home- and community-based care (Henriksen, Joseph, & Zayas-Cabán, 2009; Mickelson et al, 2016; Or et al, 2011; Or et al, 2009), we found work system factors both common and unique factors compared to hospital- and clinic-based care. The broad categories of the Workflow Elements Model seen in prior work with, for example, hospitals, emergency rooms, and ambulatory care clinics (Unertl, Johnson, & Lorenzi, 2012; Unertl et al, 2010; Zheng, Ciemins, Lanham, Lindberg, & Man, 2015), were equally applicable to the community-based mental healthcare domain.…”
Section: Discussionsupporting
confidence: 78%
“…The study identified four main actors, ten actions, and 37 unique artifacts across seven major types, all contributing to 21 possible patient care and work outcomes. Like other HFE studies of home- and community-based care (Henriksen, Joseph, & Zayas-Cabán, 2009; Mickelson et al, 2016; Or et al, 2011; Or et al, 2009), we found work system factors both common and unique factors compared to hospital- and clinic-based care. The broad categories of the Workflow Elements Model seen in prior work with, for example, hospitals, emergency rooms, and ambulatory care clinics (Unertl, Johnson, & Lorenzi, 2012; Unertl et al, 2010; Zheng, Ciemins, Lanham, Lindberg, & Man, 2015), were equally applicable to the community-based mental healthcare domain.…”
Section: Discussionsupporting
confidence: 78%
“…self-care). Some have attempted to do so, drawing examples and suggesting definitions based on prior research (Henriksen et al, 2009; Holden, Carayon, et al, 2013; National Research Council, 2011; Zayas-Cabán & Valdez, 2012). In this study, we applied the general model in Figure 1 to gather and analyze empirical data from heart failure patients and their caregivers to further develop both the idea of the patient work system and to identify the work system factors specific to heart failure self-care.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were excluded if: (1) they were not related to healthcare system redesign (e.g., Casler and Cook 2003; Wong and Richardson 2010), (2) they described best practices or methods (e.g., Beuscart-Zephir et al 2007; Henriksen, Joseph and Zayas-Caban 2009), (3) they only presented a research protocol (e.g., Hysong et al 2009; Marshall et al 2011), and (4) they reported on general quality improvement (e.g., Amoore and Ingram 2002; Mutter 2003). …”
Section: Methodsmentioning
confidence: 99%